The Management of Character-Based Holistic Education Program in Early Childhood Education (PAUD) Anak Cerdas Ungaran - Ruhaina, Nelly Ivva; Samsudi, Samsudi; Yusuf, Amin (Educational Management, 2019)
A holistic human is indicated by the growth of all development aspects. If the stimulation of early age growth and development is not optimal, it will influence the unpreparedness of entering the next education and the incomplete use of all children's competencies. The aims of this study are to deeply describe and analyze the planning, the implementation, the supervision and the evaluation as well as the implementation of character-based holistic education program in early childhood education (PAUD) Anak Cerdas Ungaran. This research used qualitative research method with case study design. The data collection techniques used in this study namely, observation, in-depth interview, and documentation. The research subjects include in this study: managers, coordinators, teachers, character coordinators, parents, students. To ensure the validity of the data this research used triangulation technique on the sources, the methods, and the theories. Data analysis was done through data reduction, data presentation, and drawing conclusion. The results showed that the planning program was based on the results of the previous year's evaluation, the implementation program was carried out through the division of teacher tasks as coordinator such as character, human resources, public relation and partnership, learning and curriculum, as well as those in charge of activities determined at the beginning of the year. The supervision was carried out during learning and teaching activities and at the end of the activities directly or in a written report. The evaluation was carried out at the end of the activities’ program by the teacher with the principal, each trimester and semester by the teacher, the principal and the manager then the final year evaluation was carried out with the coach and the expert team. The implementation program based on the Curriculum 13 PAUD combined with 9 character pillars during one school year through the several services, namely education, care, health, and protection.